Implementation of Problem-Solving Learning with Geogebra to Improve Problem-Solving Ability and Motivation - Fauzie Ridwan, Denie (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
In general, there are still many students who lack problem-solving abilities. Historically, mathematics is actually very closely related to problem-solving abilities and was developed by students as a challenge to changes in learning motivation. The world of Indonesian education has various learning models and teaching aids that can be developed, one of which is Geogebra. Geogebra can be implemented with mathematical concepts as an effort to improve problem-solving abilities. Apart from that, we can make learning motivation as fun as learning mathematics at school. Therefore, this research seeks to improve students' problem-solving abilities and learning motivation. This research uses a mixed-method research method with a sequential exploratory design type. Research data was collected through problem-solving ability tests, learning motivation questionnaires, observations, and interviews with class IX students at Mts Al-Ma'tuq Sukabumi. The results of this research show that the problem-solving abilities and learning motivation of students using geogebra-assisted learning are better than students using conventional learning. Apart from that, there is no correlation between problem-solving abilities and learning motivation of students who receive geogebra-assisted and conventional learning with a weak or low level of relationship. The contribution of this research to the development of science is to provide new insights into the application of Geogebra as a tool in mathematics learning and to reveal the importance of integrating technology to improve students' problem-solving abilities and learning motivation.